Pemanfaatan Ekosistem Mangrove dan Perubahan Lingkungan Pesisir Pulau Bawean, 1886–1923 - Novel, Muhammad (Lembaran Sejarah, 2023)
The purpose of this article is to discuss the history of mangrove ecosystem utilization and physical changes on the coast of Bawean Island during 1886 – 1923. This article used the historical method which consists of heuristic, criticism, interpretation, and historiography. Image classification and maps comparation applied as proponent system in this study to analysis coastal change. The first step is analysis data showing the activities of Bawean residents in utilizing the mangrove ecosystem. The second is analysis through image classification and map comparation to analyze historical changes. Based on this analysis, it can be seen that residents use the mangrove ecosystem for daily needs such as foundations and house roofs. Residents have also converted the function of the mangrove ecosystem into residential areas and agricultural land. Therefore, the activity of residents in coastal area as well as use of mangrove ecosystem plays a role in changing the coastal environment of Bawean Island.